The absence of [C ii] 158 μm emission in spectroscopically confirmed galaxies at z > 8. (18th June 2019) - Laporte, N; Katz, H; Ellis, R S; Lagache, G; Bauer, F E; Boone, F; Inoue, A K; Hashimoto, T; Matsuo, H; Mawatari, K; Tamura, Y
ABSTRACT: The scatter in the relationship between the strength of [C ii ] 158 μ m emission and the star formation rate at high redshift has been the source of much recent interest. Although the relationship is well established locally, several intensely star-forming galaxies have been found whose [C ii ] 158 μ m emission is either weak, absent, or spatially offset from the young stars. Here we present new ALMA data for the two most distant gravitationally lensed and spectroscopically confirmed galaxies, A2744_YD4 at z = 8.38 and MACS1149_JD1 at z = 9.11, both of which reveal intense [O iii ] 88 μ m emission. In both cases we provide stringent upper limits on the presence of [C ii ] 158 μ m with respect to [O iii ] 88 μ m. We review possible explanations for this apparent redshift-dependent [C ii ] deficit in the context of our recent hydrodynamical simulations. Our results highlight the importance of using several emission line diagnostics with ALMA to investigate the nature of the interstellar medium in early galaxies.